2016
DOI: 10.1177/1602400223
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Flexural Strength of Bone Cement Mixed with Blood

Abstract: The biomechanical strength of PMMA contaminated with blood may decrease. Precautions such as saline lavage, pack drying the bone, change of gloves, and prompt insertion of the implant should be taken to prevent blood from contaminating bone cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Nevertheless, the exact mechanism of aseptic loosening of the prosthesis has not yet been sufficiently understood. It is believed, however, that its occurrence is the combined consequence of material fatigue and chemical degradation resulting from operation in an aggressive environment in vivo [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the exact mechanism of aseptic loosening of the prosthesis has not yet been sufficiently understood. It is believed, however, that its occurrence is the combined consequence of material fatigue and chemical degradation resulting from operation in an aggressive environment in vivo [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This scenario can be prevented; however, it is critical that the cement is prepared according to the standards. The cement preparation process has undergone gradual improvement with the introduction of vacuum mixing systems, cement application guns or cooling prior to mixing, which extends the polymerisation time [19,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone-cement contamination is a problem whose effects have not yet been thoroughly studied or presented in the specialist literature. In the study by Tan et al [34], it was shown that the rate of strength characteristics degradation of blood-contaminated cements was significantly greater when the composition of the cement contained gentamicin than with its absence. The results from their study are particularly interesting given that bone-cement compositions with antibiotics introduced by the manufacturer are widely used in Europe, whereas in the United States manual antibiotic powder addition to traditional bone cement during surgery is preferred [44].…”
Section: Discussionmentioning
confidence: 99%
“…Far too little attention has been paid to the effect of contamination on the cement strength properties, in particular in the presence of human blood [34]. The focus of bone-cement studies is on admixtures of auxiliary agents, supplied to improve the material’s properties, including strength [22,26,33,35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%